Vapor–liquid–solid growth of endotaxial semiconductor nanowires - Li, Shaozhou (2013)
Free-standing and in-plane lateral nanowires (NWs) grown by the vapor–liquid–solid (VLS) process have been widely reported. Herein, we demonstrate that the VLS method can be extended to the synthesis of horizontally aligned semiconductor NWs embedded in substrates. Endotaxial SiGe NWs were grown in silicon substrates by tuning the directional movement of the catalyst in the substrates. The location of the SiGe NWs can be controlled by the SiO2 pattern on the silicon surface. By varying the growth conditions, the proportion of Ge in the obtained NWs can also be tuned. This approach opens up an opportunity for the spatial control of the NW growth in substrates and can potentially broaden the applications of NWs in new advanced fields.